Utilization of Virtual Reality: Transforming Spiritual Experiences in Hajj Ritual Learning in High Schools and Tour Travel - Basri, Hasan (Education and Talent Development Center Indonesia (ETDC Indonesia), 2025)
Secondary hajj education is often abstract and limited to physical simulations that cannot capture the Holy Land's vastness and holiness. The lack of representative Islamic religious education laboratories in Wajo Regency exacerbates this. Viewing rituals as physical procedures without inner transformation or Mecca and Medina spatial awareness lowers student spiritual engagement. This study examines how VR technology and PT Darmawan Tour & Travel can improve Wajo Regency high school students' Hajj practices and how digital immersion connects cognitive theory and affective-spiritual experiences. This study employs descriptive qualitative and collaborative case study methods. The study utilized VR devices and PT Darmawan Tour & Travel content in Wajo Regency high schools. Data is collected through participatory observation during VR simulations, in-depth interviews with professors of Islamic Religious Education and Hajj and focus group discussions (FGDs) with students. To measure spiritual presence, data reduction, presentation, and verification were done. The research indicated that VR's